ZTSCAN: ENHANCING ZERO TRUST RESOURCE DISCOVERY WITH MASSCAN AND NMAP INTEGRATION - Reikal Taupaani; Ruki Harwahyu (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2025)
Implementing Zero Trust Architecture (ZTA) requires a comprehensive understanding of network assets as a fundamental step in implementing security policies. This study proposes ZTscan, an automated tool to increase the efficiency of network asset resource discovery. This proposed tool is then made open source in Github for anyone to evaluate and extend. The research constructs a GNS3-based testing scenario to evaluate the performance of the proposed tool against other scanning tools, including standalone Nmap, Masscan, RustScan, and ZMap. The evaluation focuses on three key metrics: accuracy, scanning speed, and generated data throughput. Experimental results demonstrate that ZTscan achieves 100% accuracy, matching Nmap_Pingsyn while outperforming faster tools such as Masscan, ZMap, and RustScan in precision. ZTscan completes scans 10.64%, faster than Nmap TCP SYN scan while maintaining comparable high accuracy. In terms of throughput, ZTscan reaches a stable peak throughput that is  13.8% lower than Nmap TCP SYN scan without causing disruptive traffic spikes. The findings of this study serve as a reference for resource discovery strategies in ZTA implementation, particularly in scenarios that require fast and accurate network scanning while minimizing potential disruptions or network interference.